Islamic Educational Values in Tere Liye’s Novel Hafalan Shalat Delisa - Saida Aisyah; Fatkhur Rohman (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2026)
Islamic educational values play an important role in shaping students’ faith, worship, and moral character. Literary works, particularly novels, can serve as a medium for conveying these values through characters, plots, conflicts, and events that are closely related to readers’ lives. This study aims to analyze the Islamic educational values contained in Tere Liye’s novel Hafalan Sholat Delisa and examine its relevance as a medium for instilling Islamic values and character development. This study employs a qualitative approach using library research with a descriptive-analytic method. The primary data consist of the novel Hafalan Sholat Delisa, while secondary data are obtained from relevant books, journals, and scholarly sources. Data were collected through documentation by identifying and analyzing quotations containing Islamic educational values, followed by data reduction, data presentation, and conclusion drawing. The findings indicate that Hafalan Sholat Delisa contains three categories of Islamic educational values: aqidah, sharia, and akhlaq. The value of aqidah is reflected in faith in Allah SWT; sharia values are represented through the practice of worship, particularly prayer; while akhlaq values include devotion to parents, honesty, courage, trustworthiness, justice, wisdom, responsibility, discipline, independence, modesty, compassion, tolerance, and love for the nation. These findings demonstrate that the novel functions not only as a literary work but also has potential as a contextual medium for Islamic education in supporting the cultivation of religious values and the development of students’ character.